Endodontists on Instagram and YouTube: Content Strategies and Engagement - Bayram, E.; Bayram, H. Melike (British Journal of Healthcare and Medical Research, 2025)
Objective: This study aimed to analyze the content shared by endodontists with a high number of followers on Instagram and YouTube platforms to identify which types of content generate higher audience engagement and whether there is a significant relationship between follower count and content type. Materials and Methods: Endodontists with at least 20,000 Instagram followers and 5,000 YouTube subscribers were identified through AI-assisted screening. All posts shared by these accounts were examined, and the top ten posts with the highest likes for each account were selected. The posts were classified into four categories: educational content, clinical case presentations, technology/product promotions, and others. Statistical analyses were conducted using SPSS v19.0, with a significance level set at p<0.05. Results: Clinical case presentations achieved the highest average number of likes on both the Instagram and YouTube platforms. Educational content ranked second, while technology and product promotions exhibited the lowest engagement rates. Furthermore, a strong positive correlation was found between academic content and the number of followers on YouTube (r=0.948; p=0.050). Conclusion: Clinical case presentations and educational content are the most effective engagement tools for endodontists on social media. It is recommended that endodontists prioritize these types of content when developing effective social media strategies.